Hydraulic Efficiency Of Gully Inlets, Curbs And Combination Inlets A Systematic Review - Syahrunnizar, Nur Afiqah (Universiti Sains Malaysia, 2021)
This thesis was conducted to study the methods of determining the hydraulic efficiency of gully inlet, curb inlet and combination inlet and identify their limitation for different configurations. Nowadays, the lack of knowledge about these types of structures has not been fully overcome. Some of the studies conducted were restricted to a specific limit of parameters. Consequently, these limitations made it difficult to produce general results that apply to other types of inlets. The increasing number of studies has resulted in different approaches and methodologies to quantify the uptake process and achieve general or unified formulations with various inlets. The significant weaknesses and gaps impede hydraulic efficiency assessment and the path forward for future research. A systematic literature review was performed to aid the knowledge gap in understanding hydraulic efficiency by developing answerable review questions. The reviewed articles were conducted to answer the review questions. The basic formulation by HEC-22 overestimate the hydraulic efficiency of inlet and the developed equation is limited to certain design and parameters of the inlet.